2013
DOI: 10.1097/ta.0b013e31827e1381
|View full text |Cite
|
Sign up to set email alerts
|

Complications in acute phase hospitalization of traumatic spinal cord injury

Abstract: Prognostic study, level III; therapeutic/care management study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
69
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 26 publications
7
69
2
2
Order By: Relevance
“…This study aimed at examining the effectiveness of a multi-layer foam dressing applied to the sacral region as compared to transfer on a gel mattress in preventing pressure ulcers in patients with a traumatic SCI upon arrival at a level I SCI specialised trauma centre for the period prior to spine surgery. Nearly 19% of patients developed a PU during the acute care hospitalisation, which is within the range reported in the SCI literature (4,31). Results of this study suggest that using a multi-layer foam dressing or a gel mattress pre-operatively provide a similar effectiveness in preventing PUs in those with SCI, suggesting that the preventive dressing failed to be superior to the gel mattress in preventing sacral PUs.…”
Section: Discussionsupporting
confidence: 56%
“…This study aimed at examining the effectiveness of a multi-layer foam dressing applied to the sacral region as compared to transfer on a gel mattress in preventing pressure ulcers in patients with a traumatic SCI upon arrival at a level I SCI specialised trauma centre for the period prior to spine surgery. Nearly 19% of patients developed a PU during the acute care hospitalisation, which is within the range reported in the SCI literature (4,31). Results of this study suggest that using a multi-layer foam dressing or a gel mattress pre-operatively provide a similar effectiveness in preventing PUs in those with SCI, suggesting that the preventive dressing failed to be superior to the gel mattress in preventing sacral PUs.…”
Section: Discussionsupporting
confidence: 56%
“…3,5,6 The unadjusted rate of PU was significantly higher in patients referred from nonspecialized centers (group 2, 51.5%) as compared with patients referred from the specialized SCI trauma center (group 1, 26.7%). Similarly for patients with multiple PU, direct comparison showed that the rate was significantly more important in group 2 (24.2%) than in group 1 (2.2%).…”
Section: Discussionmentioning
confidence: 91%
“…6 Nutritional deficits, spasticity, loss of sensation, and bladder and bowel dysfunction resulting in skin moisture are also important risk factors. 3,5,7 Comorbidities, 9,12 in particular diabetes mellitus, 7Y14 as well as renal, cardiovascular, and pulmonary diseases, 13 have also been correlated to PU after an SCI. Smoking, 14Y17 low albuminemia, anemia, and advanced age have also been proposed as risk factors for PU.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The role of timing of surgical decompression after traumatic SCI is one of the most controversial subjects in spine surgery. 20,21 A current evidence-based examination of pre-clinical and clinical studies has shown that epidural decompression should be considered from 8 to 24 h following acute traumatic SCI, 4 therefore, we chose 8, 24 and 48 h to evaluate the timing of myelotomy. In this study, our results suggested that myelotomy is still effective in rats up to 48 h after SCI, while previous experimental studies mainly focused on the time points within 24 h. [6][7][8][9] In addition, we found that the potential timing of myelotomy may be between 8 and 24 h after SCI.…”
Section: Discussionmentioning
confidence: 99%